Distributed Cooperation among Cognitive Radios with Complete and Incomplete Information. (16th June 2009) - Giupponi Giupponi, Lorenza Lorenza; Ibars Ibars, Christian Christian
Abstract : This paper proposes that secondary unlicensed users are allowed to opportunistically use the radio spectrum allocated to the primary licensed users, as long as they agree on facilitating the primary user communications by cooperating with them. The proposal is characterized by feasibility since the half-duplex option is considered, and incomplete knowledge of channel state information can be assumed. In particular, we consider two situations, where the users in the scenario have complete or incomplete knowledge of the surrounding environment. In the first case, we make the hypothesis of the existence of a Common Control Channel (CCC) where users share this information. In the second case, the hypothesis of the CCC is avoided, which improves the robustness and feasibility of the cognitive radio network. To model these schemes we make use of theory of exact and Bayesian potential games. We analyze the convergence properties of the proposed games, and we evaluate the outputs in terms of quality of service perceived by both primary and secondary users, showing that cooperation for cognitive radios is a promising framework and that the lack of complete information in the decision process only slightly reduces system performance.